A construção do sentido dos enunciados : uma interface possível entre as concepções dialógica e argumentativa de linguagem - Timmermann, Rafael de Souza (2014)
This work aims to show, through analyzes of four Calvin & Hobbes comic strips (WATTERSON, 2014), the possible interface between the dialogical and the argumentative conceptions of language, in relation to the construction movement of the utterances meaning. This proposed interface, which served as a guiding question for the realization of this dissertation, was suggested in the article entitled The argumentative sequence as a donor of meaning in the dialogic discourse analysis and in the argumentative semantics (GRAEFF; TIMMERMANN, 2014b), in the journal Bakhtiniana - Journal of Discourse Studies. According to the authors, the movement performed to give the fullness of the utterances meaning in the dialogical conception of language, exposed by Voloshinov (1926/2012), in the text Discourse in life and discourse in art - Concerning sociological poetics, presents many similarities with the construction movement of the meaning defined by Ducrot (1990) in the Extended Standard phase of the Theory of Argumentation Within Language (AL), since, for both Voloshinov and Ducrot, the understanding of the full meaning of the utterance (or of the predicates that make up an utterance) is granted by extra-verbal factors, which are linguistically non-explicit, found in the world, shared by the participants of the verbal interaction. This approach has been proven through the analyzes. In them, from the lines given by the characters in the strips, the immediate (the situation) and mediate (of each character) contexts were highlighted, culminating in the verbal explanation of the presumed factors shaped as topos, thus materializing the construction movement of the utterances meaning: starting with the linguistic material, seeking an extra-verbal justification to ensure the performed conclusion. Moreover, the contribution of AL s current version, the Theory of the Semantic Blocks (TSB), was underlined ,with the inclusion of transgressive argumentative sequences and its linguistic description of the utterances meaning construction, through the semantic interdependence between the predicates of the argumentative sequence, which is considered by this theory the basic semantic unit that carries meaning. Finally the study was developed and the contribution which both conceptions of language offer a language to one another was shown